Should divorce be easier or harder? - Libertad Gonzalez (IZA World of Labor, 2014)
Many countries have enacted legislation over the past few decades making divorce easier. Some countries have legalized divorce where it had previously been banned, and many have eased the conditions required for a divorce, such as allowing unilateral divorce (both spouses do not have to agree on the divorce). Divorce laws can regulate the grounds for divorce, division of property, child custody, and child support or maintenance payments. Reforms can have a range of social effects beyond increasing the divorce rate. They can influence female labor supply, marriage and fertility rates, child well-being, household saving, and even domestic violence and crime.
Keywords: D13; J12; K36; 330; divorce; female labor supply; family law; marriage; fertility